SEMIOTICS: THE STUDY OF SIGNS - Dosen Fakultas Ekonomi, Universitas Islam Batik Surakarta, Ariviani Dewi (MAJALAH ILMIAH GEMA, 2013)
Everything can be seen as a sign as long as people interpret it as a sign. The study of a sign is what the so called Semiotics, proposed by Saussure and Pierce. This theory comes to its enormous progress in the middle part of twentieth century. Saussure and Pierce formulate Semiotic in a rather distinctive way. For Saussure, he emphasizes on its structure whereas Pierce scrutinizes on its process. Saussure is popular for its signifier and signified while Pierce is well-known for itsrepresentament, object and interpretant. Dealing with sign, human being is a smart species to be driven by a desire to make meaning. “To read” the sign, human being is the one who are in expert of meaning maker.Key words: semiotics, signifier, signified, representament, object, interpretant